Penanganan Tindak Pidana Perkara Pelanggaran Lalulintas Di Satlantas Polres Pematangsiantar - Septian Dwi Rianto; Alpi Sahari; Ahmad Fauzi (Mahesa Research Center, 2020)
Traffic violations have become a habit of the road user community, so that every time an orderly operation of the traffic on the road is carried out by the authorities, traffic violation cases are still occurring and these violations often cause traffic accidents. The research method used in this research is to use a normative and empirical approach. i.e. conducts library research by researching and collecting library materials that are specifically related to laws and regulations and books relating to law and traffic, as well as field research conducted by observing observations and direct interviews with related objects. The results showed that the forms of traffic violations that occurred were motorists breaking traffic signs, driving not using a complete safety system. Some acts and sanctions for violations which are categorized as traffic violations regulated by Law No. 22 of 2009. Factors handling obstacles to traffic violations in Siantar Traffic Police Station Siantar, namely the human factor (Human Error), the factor of inadequate road infrastructure and facilities causing traffic violations. Efforts to deal with traffic offenses at the Siantar Police Traffic Police Unit are preventive and repressive measures to take action by giving a letter of reprimand or verbally, taking action by giving a ticket.